The Effectiveness of Role-Play Basic Life Support Training in Improving Knowledge and Attitudes Toward Cardiac Arrest Among the Laypersons - Misbah Nurjannah; Herdianti Herdianti; Wenty Amelia; Afifah Nur Madaniya; Taharuddin Taharuddin (Yayasan Ahmad Mansyur Nasirah, 2026)
Out-of-hospital cardiac arrest (OHCA) remains a leading cause of death worldwide, and early Basic Life Support (BLS) provided by laypeople is critical for improving survival before emergency medical services arrive. However, public knowledge and attitudes toward BLS remain inadequate because many individuals have never received formal training. This study aimed to evaluate the effectiveness of role play-based BLS training in improving laypeople’s knowledge and attitudes toward cardiac arrest first aid. A quasi-experimental one-group pretest–posttest design was conducted among 68 lay participants recruited through consecutive sampling. Participants received role play-based BLS training, and knowledge and attitudes were assessed using structured questionnaires before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test, with additional analyses examining associations between demographic characteristics and study outcomes. Following the intervention, participants demonstrated significant improvements in both knowledge and attitudes. The proportion with good knowledge increased from predominantly moderate (63.6%) to 97.0%, while positive attitudes increased from 72.7% to 93.9%. Significant differences were observed in knowledge and attitude scores (both p < 0.001), with a large intervention effect (r = 0.62). No significant associations were found between demographic factors and outcomes. Role play-based BLS training effectively improves laypeople’s knowledge and attitudes regardless of demographic characteristics, supporting its implementation as an inclusive, practical strategy to strengthen community preparedness for cardiac arrest emergencies.